Crystallographic and Geometrical Dependence of Water Oxidation Activity in Co-Based Layered Hydroxides - Sanchis-Gual, Roger; Hunt, Diego; Jaramillo, Camilo Juan; Seijas Da Silva, Alvaro; Mizrahi, Martin Daniel; Oestreicher, Víctor; Abellán, Gonzalo (American Chemical Society, 2023)
Fil: Sanchis-Gual, Roger. Instituto de Ciencia Molecular(icmol); España